Deliberative future visioning: utilizing the deliberative democracy theory and practice in futures research - Hanna-Kaisa Pernaa (European Journal of Futures Research, 2017)
Abstract Broadly defined, deliberative democracy aspires the decision-making legitimacy by deliberation of equal citizens. As a response to the growing discontent with the representational governance, the normative and empirical development of the deliberative democracy theory addresses the increasing desiderata of public engagement beyond party politics and constituencies. Generating knowledge for the use of policy-making, foresight shares a common ground of participative and policy-impacting challenges with the deliberative democracy theory. In this article the prospects and mutual advantages of deliberative democracy (DD) alliance with the field of futures studies are discussed. The exploration strives to accentuate the societal policy-making advantages of the cross-disciplinary development. The article begins with introducing the deliberative democracy theory and the theoretical development, following with an account of some encouraging deliberative practices. A brief sketch of two recent projects enhancing participation detail the discrepancies in defining the concept. After examining the common epistemic ground of futures studies and social studies, the cross-disciplinary interface and shared key elements in policy-making impact are described. The article proposes a multi-voiced and future-oriented dialogue as a prerequisite for ameliorating societal preparedness and resilience in a world marked by proliferating uncertainty.